Wind power reliability valuation in a Hydro-Dominated power market: The Colombian case (2016)
The design of market mechanisms that remunerates the reliability provided by a generator in a power market is a task that aims to ensure the normal operation of the system. For the case of a Hydro-Dominated system, when wind power is introduced and operated under the Merit-Order-Effect, it is possible to assess the effect of the displacement of hydro generation due to wind generation over the system's reliability in terms of firm energy; taking this into account a model that valuates the firm energy provided by wind power in a hydro-dominated system is proposed. This model considers the effect of wind power over the system's reservoirs and the market price of electricity; and valuates the firm energy as the net savings of the system related to the increase in the firm energy of the system when wind power is introduced. The results show that wind power under Merit-Order-Effect increases the firm energy of the system, and decreases the market price of electricity, being the net savings in comparison to the corresponding hydro-only system the reliability income that should be perceived by the wind power generator. © 2016 Elsevier Ltd. All rights reserved.